Synthesis and characteristics of modified polyamides based on lactames and polyetheramines - Dutkiewicz, S.; Boryniec, S. (Polimery, 2022)
Conditions of the syntheses, by anionic polymerization method, of homo- and copolyamides based on epsilon-caprolactam (KL) and kappa-lauryllactam (LL) modified with urea prepolymers (Table 2), obtained from tolylene diisocyanate and three various polyetheramines (polyoxyethylenediamine, poly- oxypropylenediamine or polyoxypropylenetriamine - Table 1) have ben described. An introduction of flexible polyether segments into the polyamide chain has been done with the aim to increase the impact resistance. The effects of the type of amine used and copolyamides KL/LL compositions on the chosen mechanical properties (stress at break, elongation at break, impact resistance at temp. 20degreesC and 40degreesC) as well as on the contents of non-polymerized components (soluble in acetone) have been determined (Tables 3-6). Expected substantial improvement of impact resistance was reached only in the case when polyoxypropylenetriamine was used.